Operation Strategies of a Solar Trigeneration Plant in a Residential Building - Ines Horvat; Dominik Grubišić; Ante Marušić; Dražen Lončar (Journal of Sustainable Development of Energy, Water and Environment Systems, 2021)

(untitled)
Actual trends of increased utilization of renewable sources in residential sector impose new requirements for domestic energy system operation. Recent research results have shown that a high level of energy autonomy could be achieved by the utilization of such systems in a residential building located within the European continental climate zone. That is particularly interesting in the light of the fact that in near future access to the hourly electricity market will be enabled to all households thus acting as prosumers. In this paper, the energy system comprising of a photovoltaic thermal collector, heat storage, heat pump and auxiliary energy sources, sized to cover the most of electricity, heating and cooling demand of a selected low-energy family house (180 m2 heated and cooled area, 75 m2 useful roof area, located in northwest Croatia) was considered. By analysis of yearly operational profiles, required exchange of energy on electricity market was estimated. Detailed mathematical model of the system was used for hourly simulation in order to evaluate impact of operational strategies on both renewable energy sources utilization and profitability. Two different control strategies were compared in typical days defined by profiles of energy demands, solar irradiance and electricity price. The simulation results showed how the change in operation strategy can reduce operational cost.